The Strategy of Muslim Communities in Encountering Islamophobia in The United States - Hasbi Aswar (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2021)
The number of Muslims in the United States is increasing from year to year as a result of the increasing number of immigrants from Muslim countries who come to work and continue their education as well as the increasing number of Muslims. One of the problems faced by the Muslim community in America today is Islamophobia such as bad narratives, discrimination, and violence against Muslims and their property. This study will examine the role of the Muslim community in America in dealing with the phenomenon of Islamophobia by explaining its strategy through the concept of Non-Governmental Organizations. The data used in this study is literature collected online from websites of Islamic groups in the United States. The results of this study showed that Islamic groups have taken many ways to deal with Islamophobia in this country, namely through political and legal advocacy, media relations, education, and campaigns to garner support and introduce Islam in American society.